A novel hybrid MCDM approach for selecting sustainable alternative aviation fuels in supply chain management. (1st November 2022) - Chai, Naijie; Zhou, Wenliang
Highlights: Select sustainable alternative aviation fuels (AAFs). Take into account decision-makers' (DMs') risk preference. Develop a hybrid five-phase decision-making approach. Use four sustainable AAFs to illustrate and verify its application and rationality. Abstract: The selection of sustainable alternative aviation fuels (AAFs) plays an essential function in the success of fuel supply chain management. Traditional and classical multi-criteria decision-making (MCDM) methods are contributed to making decisions under a deterministic condition, and assume that decision-makers (DMs) are absolutely rational when coping with various risks. Nevertheless, it is difficult that these hypotheses are applied in the process of complex AAF evaluation. The complexity associated with the AAFs' sustainability evaluation primarily origins from the fuzzy and ambiguous assessment information, DMs' subjective preferences, different opinions and thoughts among DMs with respect with criteria. Unfortunately, previous studies failed to solve these problems thoroughly. To fill such a gap, a novel hybrid five-phase fuzzy MCDM approach is put forward by integrating interval valued triangle fuzzy numbers (IVTFNs), IVTFN-AHP, IVTFN-TOPSIS, and cumulative prospect theory in this study. It can effectively deal with uncertainty in this process, particularly the cumulative prospect theory enables to well depict DMs' risk preference of and expresses their actual opinions. Afterwards, four alternative aviation fuels (i.e., Algal-based fuel (A1), Petroleum refining (A2), Soybean -based fuel (A3), and Fischer-Tropsch synthesis based on natural gas (A4)) are studied to illustrate the application of the proposed method, the results demonstrate that the sustainability order from the best to the worst determined based on the opinions of the five groups of DMs is A1, A3, A2, and A4, meaning that Algal-based fuel achieves higher energy efficiencies and fewer greenhouse gas emissions than other alternative fuels. In order to further investigate the robustness and rationality of this approach, sensitivity analysis and comparative analysis are also carried out in this study.